إدارة السيولة في المصارف الإسلامية : ماليزيا نموذجا - Mohamad Sabri Zakaria (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
Liquidity and its management are considered to be among the most important issues of concern among researchers on banking practices, particularly those used in contemporary Islamics banks. This is because Islamic banking is relatively new while the usury-based conventional system has been in place for so long. Consequently, it is not easy for Islamic banks to manage liquidity in view of the hostile surroundings that they have to deal with. Thus, while conventional banks are able to use the established mechanism to manage liquidity-which are mostly based on usury, Islamic banks, on the other hand, find the door shut before them in this regard because they have to maintain – by default-their special characteristics which include a total and absolute opposition to usury. This principle invariably leads to strong reservations about liquid investing due to the lack of Islamic investment vehicles in the market. As a result, they face the problem of liquidity surplus- a factor which inevitably limits the size of their profits. In light of this, there is a great need for Islamic alternatives to manage liquidity in Islamic banks, and this research is specifically designed to address this problem. Hence it considers the concept liquidity from an Islamic perspective explores the mechanism of managing liquidity in the conventional banks and discusses the extent of their conformity to the shari'ah. In addition, the study also examines the Malaysian experience in term of how the Islamic banks in this country manage liquidity. In this respect, it is found that there are certain instances of divergence from the Islamic principles in their practices. This must be corrected by resorting to mechanism that conform to the shari'ah in managing liquidity at each bank. This research uses the analytical method whereby the jurists' opinions on various related issues are analysed. It also takes into account the critical method to discuss issues that are based on ijtihad. In doing so, it has benefited from looking at the real practices that are in place at the Islamic banks which are constantly attracting interest locally and abroad.